OPTIMALISASI ETIKA PROFESI GURU DALAM MENCIPTAKAN LINGKUNGAN SEKOLAH ANTI-BULLYING - Anni Latifah; Angel Tio Lina Aritonang; Esrawati Napitupulu; Melva Triana Sianipar; Nazwa Sabila Sitepu; Nira Dilvinia Siregar; Wulan Fitri Andini Siahaan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Bullying in the school environment remains a serious issue that affects students’ psychological, social, and academic development. This phenomenon indicates that prevention efforts have not been optimally implemented, including the application of teachers’ professional ethics. Teachers, as educators and role models, have a strategic role in building a safe and character-based school culture. This study aims to analyze the optimization of teachers’ professional ethics in creating an anti-bullying school environment. The method used is a qualitative approach through a literature study and descriptive analysis of regulations, the teachers’ code of ethics, and educational practices in schools. The results of the study indicate that strengthening integrity, exemplary behavior, consistency in enforcing rules, and collaboration among teachers, students, and parents are key factors in preventing bullying. The optimization of teachers’ professional ethics functions not only as a moral guideline but also as a strategic instrument in building an inclusive and humane school culture. Therefore, strengthening teachers’ professional ethics needs to be carried out systematically through training, continuous evaluation, and internal school supervision in order to create a safe and dignified educational environment.